HUZEYFE BİN YEMAN VE PEYGAMBER EFENDİMİZ'DEN ÖĞRENDİĞİ ÖZEL BİLGİLERLE İLGİLİ RİVAYETLERİN DEĞERLENDİRİLMESİ - KAZAK, NESİBE (Fırat Üniveristesi, 2009)
Bu çalışma, Ashab'ın güzide isimlerinden olan, Hz. Peygamber'in sır arkadaşı olarak bilinen, Huzeyfe b. Yeman'ın hayatıyla birlikte, Peygamber Efendimiz'in sadece O'na söylediği özel bilgiler olan gaybi hadisleri içerir. Gaybî konular, akıl ve duyular ile bilinemeyecek olağanüstü bilgilerdir. Bu sebeple insanoğlunun hep merakını çekmiştir. Zihinleri meşgul eden bu konu âyet ve özellikle Huzeyfe b. Yeman'ın rivayet ettiği hadislerle açıklanmıştır. Özetle bu çalışmada bir sahabenin rivayetleriyle gayb konusu incelenmiştir.

This work includes the life of Huzeyfe bin Yeman who was known as the intimate friend of our Prophet and our Prophet Mohammed?s very special sayings called unknown sayings that were told to only him. Unknown sayings(subjects) are unnatural knowledge that are not seen, heard or comprehended by mind. That is why the unknown subjects take the attentions of the people all the time. This subject occupying minds were explained with the Verses of the God and Verses of the Prophet Mohammed told especially by Huzeyfe bin Yeman.. To sum up, In this work, it was examined about the life of a sahabe(a person who saw The Prophet Mohammed) and unknown subjects.
Huzeyfe b. El- Yeman and with unknown to interested news
Keywords: Din